25+ Projects with AJAX, JavaScript, and JSON - Svekis, Laurence (Packt Publishing, 2021)
Build your own JavaScript mini projects with this full stack JavaScript coding course About This Video Create dynamic data-driven web applications with JavaScript and boost the performance of your web pages Create interactive web content generated from JSON data Learn to connect to web APIs and make AJAX requests with JavaScript In Detail AJAX allows you to communicate with the server, exchange data, and update the page without having to refresh the page. The two major features of AJAX allow you to do the following: Make requests to the server without reloading the page Receive and work with data from the server This course is loaded with 25 plus mini projects to help you learn and practice connecting to endpoints, returning JSON data, making fetch requests, using JSON data with JavaScript to create page content, and explore GET POST PUT and DELETE with JavaScript AJAX. Learn how to create and manipulate page elements with modern JavaScript code to build interactive and fully dynamic web applications driven by JSON data. Get user selections, make the AJAX request from the user select, and output to the web page using JavaScript code. Explore fun interactive projects to make AJAX requests coming from page data and output the content to the page. Dynamic page elements generated from AJAX requests to endpoints and return JSON data and use it within JavaScript to update and manipulate DOM page elements. Create games, get JSON data, and let users explore the data. Dynamically generate page content with JavaScript. Connect to web endpoints - get JSON data and output that content into your web page with JavaScript. AJAX practice mini projects will help you learn more about JSON data such as making fetch requests, debugging, and more. Who this book is for This course is for modern web designers and web developers; anyone who wants to learn how to load JSON data and apply the contents to their web pages and learn more about making AJAX requests via JavaScript; JavaScript coders who want to learn more about AJAX; and individuals who want to learn more about JavaScript fetch and modern request methods.